Designing A Model to Investigate The Role of The Factors Formulation Public Policies In The Implementation of The Administrative System Health Policy - Niknamian, Sorush (Quantitative Economics and Management Studies, 2020)
The purpose of this study is to design a model to investigate the role of the Individuals making public policies in the implementation of the administrative system health policy. Two questionnaire has been used in the current study: One whose main aim was to investigate the actors making public policy with 51 questions and Cronbach Alpha 0.93, and the other one in the administrative system health policy with 74 questions and Cronbach Alpha 0.95. To be assured with regard to the validity of the questionnaires content and construct validities were estimated. The statistical population of the current study were 86643 employers of the executive organizations of the Khuzestan province, Iran. The final sample of the study was 382 individuals based on Cochran. Data analysis was done by using SPSS 22 and Amos 22. The results of the current study revealed that the factors making the public policy included 13 factors in which the most average was for mass media (7.64) and the least was the powerful elites with the mean of (5.64). The health administrative policies included 14 policies, all of them were at significant point except the policies of eleventh to thirteenth of the fifth book â€œIslamic Panel Codeâ€, the law of banning more than on job, and the principles of prevention and fighting against bribe. The results also showed that there was a statistically significant relationship between the factors making public policy and those of administrative health policy.